Konsep Kebahagiaan Perspektif Thomas Aquinas dan Hamka dalam Pemaknaan Santri Al-Ihsan Cibiru - Khalid Al Ghozi (UIN Sunan Gunung Djati Bandung, 2023)
In general, today’s society emphasizes happiness as a goal that must be achieved in life, so that now there are many who emphasize happiness only in worldly life. Until now there are still many researches on happiness because each individual interprets happiness differently according to the background or condition of the person. Recent research studies state that not all concepts or theories can suit the situation and conditions of society. This research aims to find out how Thomas Aquinas and Hamka’s views on the meaning of happiness and find out how a Al-Ihsan Cibiru student interprets happiness. This study used a qualitative method by collecting bibliographical sources and interviews as well as observations, both primary and secondary data. The results and discussion in this study found similarities in the concept of happiness by Thomas Aquinas and Hamka, namely to achieve true happiness, closeness to God and accompanied by moral virtual and the two figures equally emphasize happiness to divine (God). This research concludes that indirectly Al-Ihsan Cibiru students use Thomas Aquinas and Hamka’s concept of happiness in interpreting happiness. It can be seen from the answers that mostly refer to devotion to Allah SWT which is in line with the concept given by Thomas Aquinas and Hamka.